The world of jade - Markel, Stephen (Bombay [Mumbai] : Marg Pub., 1992)
Contributed articles; cover Chinese, Islamic, Indian, European, pre-columbian, and New Zealand jades
Includes bibliographical references
Keywords: Jade art objects -- Asia; Jade art objects -- New Zealand